2018
DOI: 10.3389/fphar.2018.01430
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Risk and Incidence of Immune Checkpoint Inhibitors Related Pneumonitis in Patients With Advanced Cancer: A Meta-Analysis

Abstract: Background: Recently, immune checkpoint inhibitors (ICIs) have been proved one of the most promising anti-cancer therapy, series clinical trials have confirmed their efficacy. But they are also associated with distinctive set of toxic effects, which are recognized as immune-related adverse events. Among those immune-related adverse events, pneumonitis is rare, but it is often clinically serious and potentially life-threatening. Although many clinical trial results of PD-1/PD-L1 inhibitors had been reported inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 58 publications
6
71
1
1
Order By: Relevance
“…https://doi.org/10.1183/16000617.0058-2019 study on NSCLC only [59], the ICI-P incidence was 4.8% (3.8-5.7%) for all grades and 2.0% (2-2.9%) for grades 3-5. In a third study [58], the frequency of ICI-P is 2.6% (1.7-3.8%) for all grades and all tumours.…”
Section: Frequency Of Pneumonitis In Patients Receiving Icismentioning
confidence: 81%
See 1 more Smart Citation
“…https://doi.org/10.1183/16000617.0058-2019 study on NSCLC only [59], the ICI-P incidence was 4.8% (3.8-5.7%) for all grades and 2.0% (2-2.9%) for grades 3-5. In a third study [58], the frequency of ICI-P is 2.6% (1.7-3.8%) for all grades and all tumours.…”
Section: Frequency Of Pneumonitis In Patients Receiving Icismentioning
confidence: 81%
“…Clarifications provided by systematic reviews and meta-analyses on irAEs In December 2018, several systematic reviews conducted on irAEs [21,22,[50][51][52][53][54] and, more specifically, on respiratory adverse events including ICI-P [55][56][57][58][59][60], involved nine to 48 randomised controlled prospective trials including 3500-15 000 patients. These studies involved patients with either any cancer type [22, 50-55, 57, 58, 60] or only NSCLC [21,56,59], treated either with any ICI [22, 50-52, 55, 57, 60] or only anti-PD-1/PD-L1 inhibitors [21,53,54,56,58,59]. These studies present significant methodological differences, with epidemiological data on ICI-P summarised in table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, although several meta-analysis have evaluated the efficacy and safety of ICIs (Wang et al, 2017;Barroso-Sousa et al, 2018;Ma et al, 2018;Wang et al, 2018;You et al, 2018), most studies included chemotherapy as the control group for the analysis, and few studies specifically assessed the safety of ICIs. A published meta-analysis by Wang et al in 2018 reported fatal toxic effects associated with ICIs.…”
Section: Introductionmentioning
confidence: 99%
“…The association between gut microbiota and the lung immune system may be critical in the treatment outcome of lung cancer . Moreover, various drugs are prone to cause interstitial pneumonia (IP) in lung cancer patients, at least in part through immunological mechanisms . However, little is known about the effects of probiotics on drug‐induced IP in cancer patients.…”
Section: Introductionmentioning
confidence: 99%